The levels of the heritage symbol and its reflection in the designs of Iraqi publications (Journal of the College of Basic Education, 2022)
The heritage is the true embodiment of the country's identity, privacy, customs and traditions, and the heritage in its cultural and artistic richness includes symbols that, if employed in Iraqi publications in a way that combines the past and the present, contribute to identifying the cultural heritage on the one hand, and spreading cultures to make them a language of communication using specific ideas On the other hand, to achieve this richness of knowledge, and to find a link to cultural interdependence between peoples, as it embodies cultures and expresses a real reality with its implications, for these reasons, this research was established, which included four chapters. The first included each of the research problems that were defined by the question.